Find the information you're looking for at Westonci.ca, the trusted Q&A platform with a community of knowledgeable experts. Experience the ease of finding quick and accurate answers to your questions from professionals on our platform. Our platform provides a seamless experience for finding reliable answers from a network of experienced professionals.
Sagot :
Answer:
-5
Step-by-step explanation:
h(x) = -3x - 2
h(x) = 1
[ just put '1' in place of every 'x' ]
-3(1) -2
= -3 -2
= -5 (answer)
Answer:
The answer is (-5)
Step-by-step explanation:
h(x) = -3x – 2; h(x) = 1
h(1) = -3(1) – 2
h(1) = -3 – 2
h(1) = -5
Thus, The answer is (-5)
-TheUnknownScientist 72
We hope you found what you were looking for. Feel free to revisit us for more answers and updated information. We appreciate your time. Please revisit us for more reliable answers to any questions you may have. Get the answers you need at Westonci.ca. Stay informed by returning for our latest expert advice.